Indonesia’s Aggression in East Timor: The Question of Political Justification - Ayunitias, Joana Meila (Dialogi Polityczne, 2023)
Indonesia’s aggression towards East Timor started in 1974 and lasted for more than two decades. There was none to little interventions by the international governments during the first two years of the aggression which caused its long period. Indonesia’s decision to intervene in East Timor’s independence met with reluctant diplomatic response by the international world as East Timor’s winning political party used communism as its ideology. Neoclassical realism is used to analyze the domestic situation and how it was later translated into international response in Indonesia’s aggression to East Timor. East Timor’s aggression is a systemic result of an individual’s obsession and matched with international ignorance – especially the West in this regard. At the end of the day, East Timor was a victim of both Indonesia’s foreign policy and ideological war during the Cold War.